Legal Pluralism and customary law in Andean communities: The case of the Casaorcco community, Ayacucho, 2020 - López, Juan Ramos; Gomez, Jim Rivelino Paucca; Orellana, Félix Rojas (Edelweiss Applied Science and Technology, 2025)
In the community of Casaorcco, Ayacucho, customary law remains the primary mechanism for conflict resolution, coexisting with state law within a framework of legal pluralism. This study examines its role in the administration of justice, its theoretical foundations, and its impact on social cohesion and communal autonomy. Through a qualitative and ethnographic approach, including interviews with 62 community members (among them 8 leaders) and documentary analysis, it was found that the communal assembly is the main authority, imposing sanctions such as cold-water baths with nettles and communal labor. While these practices reinforce cultural identity and social order, they also spark debates regarding the proportionality of punishments and their compatibility with human rights. Communal justice, based on collective participation, lacks written regulations, leaving room for arbitrariness and tensions with state law. In this context, it is essential to articulate both systems through intercultural dialogue that balances communal autonomy with respect for fundamental rights, ensuring fair and culturally relevant justice.